The graphic user interface of the AudioGraph Recorder (PC version) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Computer Science at Massey University - Nie, Shao H (Massey University, 2001)
With the popularity of the use of computers and the development of the Internet, many multimedia-authoring systems have been developed for computer-based teaching and learning. This is playing an increasingly important role in education. One authoring system is the AudioGraph project developed at Massey university of N.Z., which have been developed for recording audio-graphic presentation material for publication in an html reference environment, i.e. "on the web". One of the tools in the AudioGraph project is the AudioGraph Recorder, which is a Macintosh application for recording or authoring web-based multimedia presentations. Due to the success of the publication of the AudioGraph application and the need of PC users, an AudioGraph Recorder for the PCs is required. This project is about the porting of the AudioGraph Recorder from the Macintosh platform to the PC platform. First this project report explains the functionality of the AudioGraph Recoder (the Macintosh version), especially how the end users interact with the interface of the AudioGraph Recorder, and the corresponding state changes of the controls in the interface. Then the report compares the development tools used in both platforms. The Macintosh version of the AudioGraph Recorder has been developed with the PowerPlant framework in CodeWarrior environment, but the PC version uses MFC framework in Visual C++ 6.0. This report also describes in detail how the interface of the AudioGraph Recorder application was constructed with the MFC, and implementation of some functionality of the application. At the same time some internals of the MFC framework are discussed.
Keywords: Computer systems; Graphical user interfaces